IMPLEMENTING INSTAGRAM-BASED SCHOOL PROMOTION: A QUALITATIVE CASE STUDY OF PUBLIC RELATIONS MANAGEMENT - Nyimas Atika; Dela Sintia; Lia Efriliyanti (EDUCATIONE, 2026)
Competition among educational institutions in the digital era requires madrasahs to communicate their institutional value, achievements, and services through media that are accessible, visual, and interactive. MTs Negeri 1 Palembang has used Instagram as a school-promotion platform, yet its implementation still faces managerial constraints related to human resources, time allocation, and content consistency. This study aims to analyze how Instagram-based school promotion is implemented at MTs Negeri 1 Palembang and to identify the constraints and solutions encountered by the public relations team. The study employed a qualitative case study design. Data were collected through observation, semi-structured interviews with key informants directly involved in promotion activities, including the Deputy Head of Madrasah for Public Relations and Instagram administrators, and documentation of school Instagram content, captions, comments, promotional materials, and school activity archives. The data were analyzed through data condensation, data display, and conclusion drawing, while credibility was strengthened through source and technique triangulation. The findings indicate that Instagram promotion was implemented through four public relations management functions: coordination, motivation, communication, and direction. Coordination ensured the availability of activity information and documentation; motivation supported continuity despite limited staff and time; communication connected internal information flows with public interaction; and direction maintained appropriate language, content selection, and institutional image. The main obstacles were the absence of a dedicated social media team, limited upload scheduling, and weak performance evaluation. The study concludes that Instagram-based promotion should be managed as an institutional public relations system, not merely as a posting activity, through clearer role distribution, content governance, posting calendars, and engagement evaluation.